Strategi Efektif Pengelolaan Kelas untuk Meningkatkan Kualitas Pembelajaran di Sekolah Dasar - Nailus Sabila Firdausiyah; Mufidatul Rosidah; Nayla Samitha Ramadhani; Muhammad Zaki Bahtiar; Ahmad Aril Athok Illah; Mu’alimin Mu’alimin (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Classroom management is a crucial aspect in creating a conducive learning environment, both in face-to-face and online learning. These articles discuss various classroom management strategies and approaches applied at various levels of education, from elementary school to college. Some of the main findings include: 1). The Importance of Planning and Organizing 2). Inhibiting Factors and Solutions 3). The Role of Teachers and the Learning Environment 4). Recommendations for Improvement Good classroom management not only improves the effectiveness of learning but also encourages active participation of students. Further research is needed to develop a classroom management model that is adaptive to technological developments and educational needs in the digital era.